2016
DOI: 10.1136/annrheumdis-2015-207655
|View full text |Cite
|
Sign up to set email alerts
|

Acute serum amyloid A is an endogenous TLR2 ligand that mediates inflammatory and angiogenic mechanisms

Abstract: A-SAA is an endogenous ligand for TLR2, inducing pro-inflammatory effects in RA. Blocking the A-SAA/TLR2 interaction may be a potential therapeutic intervention in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…However, Connolly et al . showed that SAA activated nuclear factor‐κB through Toll‐like receptor (TLR)2, not TLR4, in human embryonic kidney cells . Generally, NLRP3 is activated by TLR4 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, Connolly et al . showed that SAA activated nuclear factor‐κB through Toll‐like receptor (TLR)2, not TLR4, in human embryonic kidney cells . Generally, NLRP3 is activated by TLR4 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The UAS scores were determined as daily (minimum = 0; and maximum = 6) and over 4 days (sum of the daily score values; minimum = 0; maximum = 24). The UAS was graded as: mild (0-8), moderate (9-16), and severe (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Urticaria Activitymentioning
confidence: 99%
“…To date several receptors, including FPRL-1 [21], TLR2 [26,51] and TLR4 [28], receptor for advanced glycosylation end products (RAGE) [44], as well as class B scavenger receptors, SR-BI and CD36 [24,25,42], have been identified as SAA receptors that mediate its various functions. Our previous findings revealed that SR-BI and CD36, the most well–characterized members of SR-B family, could function as SAA receptors mediating its uptake and signaling in epithelial cells overexpressing these two proteins.…”
Section: Discussionmentioning
confidence: 99%